2021
DOI: 10.1186/s12969-021-00529-x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile primary fibromyalgia syndrome: A Review- Treatment and Prognosis

Abstract: Juvenile primary fibromyalgia syndrome (JPFS) is a chronic musculoskeletal pain syndrome affecting children and adolescents. In part one of this review, we discussed the epidemiology, etiology, pathogenesis, clinical manifestations and diagnosis of JPFS. Part two focuses on the treatment and prognosis of JPFS. Early intervention is important. The standard of care is multidisciplinary, combining various modalities—most importantly, exercise and cognitive behavioral therapy. Prognosis varies and symptoms may per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 99 publications
(112 reference statements)
0
14
0
Order By: Relevance
“…Additionally, although most studies have focused on investigating FM in adults, its occurrence has also been reported in children and adolescents. 16,17 Therefore, this study contributes to the understanding of this pathology in juvenile individuals, because we used prepubertal animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, although most studies have focused on investigating FM in adults, its occurrence has also been reported in children and adolescents. 16,17 Therefore, this study contributes to the understanding of this pathology in juvenile individuals, because we used prepubertal animals.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to better understand the regulation of muscle mass in a non‐inflammatory hyperalgesia model and the potential contribution of glucocorticoids in controlling protein metabolism in skeletal muscles, as well as nociception in female rats subjected to the FM model. Additionally, although most studies have focused on investigating FM in adults, its occurrence has also been reported in children and adolescents 16,17 . Therefore, this study contributes to the understanding of this pathology in juvenile individuals, because we used prepubertal animals.…”
Section: Discussionmentioning
confidence: 99%
“…Previously referred to as 'central pain,' the symptom hallmarks include diffuse hyperalgesia (increased pain to normally pain stimuli) or allodynia (pain to normally nonpainful stimuli). CNS-derived symptoms, including fatigue, nonrestorative sleep, cognitive dysfunction, memory, and mood disturbance, are common [7][8][9].…”
Section: Fibromyalgia and Nociplastic Painmentioning
confidence: 99%
“…In general the onset of JFS is recorded during early adolescence, younger children are also identified [4]. The mean age of diagnosis is 14.5 14.5 years, although the range is 5 to 18 years overall [5]. The average age of diagnosis is 14.5 14.5 years, although the range is from 5 to 18 years.…”
Section: Introductionmentioning
confidence: 98%